IMPLEMENTASI KEWAJIBAN PEMERINTAH DALAM MEMBERIKAN PERLINDUNGAN KHUSUS KEPADA ANAK KORBAN KEJAHATAN SEKSUAL BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK DI KOTA PEKANBARU - Tri Meri Handayani; Emilda Firdaus; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Children as the gold of the future and future generations of the ideals of national development Indonesia have human rights that must be protected from crimes, especially immoral acts in accordance with Article 1 point 2 of the Basic Law Number 35 Year 2914 concerning Amendments to Law No. 23 of 2022 concerning child protection. The large number of cases of sexual abuse against children has made the central and local governments only think about sanctions by the perpetrators, political parties are everywhere and even indifferent to the increasing cases of child abuse without thinking about how to provide protection and rehabilitation both psychologically and socially to children and their families victims of social acts. The purpose of writing this thesis, namely: first, to find out how the government's obligation to provide special protection for child victims of sexual crimes based on Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. Second, to identify obstacles and government efforts in providing special protection for child victims of sexual violence. This type of research can be classified in the type of sociological judicial research, because in this study the author directly conducted research at the location or place under study to provide a complete and clear picture of the problem under study. This research was conducted at the Department of Women's Empowerment and Child Protection in Pekanbaru City at Jln. Dagang No. 78 Pekanbaru, while the population and sample are all parties related to the problem studied. Sources of data used include primary, secondary and tertiary data. The collection technique used a questionnaire, interview, and literature study.Keywords: Goverment Implementation-Child Immoral Acts